Neo-industrialization and “Servitization”: Is There a Contradiction? - S. A. Tolkachev; A. A. Bykov; N. M. Gluhova (Мир новой экономики)
Taking into account the results of the study outlined in the 2017 World Bank Group’s Global Value Chains Development Report, the authors considered the main factors of the growth in the share of services in international trade and defined the concepts of direct and indirect value-added services in exports. Further, the authors calculated the indicators of international trade statistics for value-added for Russia and other countries. A method for estimating the share of services in exports according to the national standard for inter-sectoral balance, as well as approaches to the description of national value chains of services, is proposed. International comparisons are carried out in the context of these indicators. Indicators (the share of direct and indirect services in exports, the share of IT services in intermediate consumption of services) prove that Russia is approaching the world average. However, investment in the intellectual property of Russia is much lower than in other countries of comparable size. It can lead to underproduction of intellectual services. The growth in the share of services is a global trend and is not the result of de-industrialisation. Information and communications services help accelerate the growth of manufacturing industries, including machinery and equipment.